A Dual Physical Cross‐Linking Strategy to Construct Tough Hydrogels with High Strength, Excellent Fatigue Resistance, and Stretching‐Induced Strengthening Effect. Issue 7 (31st May 2021) - Yang, Qianyu; Gao, Chen; Zhang, Xuemei; Tsou, Chihui; Zhao, Xingyu; De Guzman, Manuel Reyes; Pu, Zejun; Li, Xinyue; Lu, Yue; Zeng, Chunyan; Yuan, Li; Xia, Yiqing; et al.
Abstract: Hydrogels with excellent stiffness, toughness, anti‐fatigue, and self‐recovery properties are regarded as promising water‐containing materials. In this work, a dual physically cross‐linked (DPC) sodium alginate (SA)/poly[acrylamide (AAm)‐acrylic acid (AAc)‐octadecyl methacrylate (OMA)]‐Fe 3+ hydrogel is reported, which is constructed by hydrophobic association (HA) and ionic coordination (IC). The optimal DPC hydrogel demonstrates excellent mechanical performance: tensile modulus of 0.65 MPa, tensile strength of 3.31 MPa, elongation at break of 1547%, and toughness of 27.8 MJ m –3 . SA/P(AAm‐AAc‐OMA)‐Fe 3+ DPC hydrogels also exhibit prominent anti‐fatigue and self‐recovery performance (99.1–109.7% modulus recovery and 90.4–108.9% dissipated energy recovery after resting for 5 min without additional stimuli at ambient temperature) through the reconstruction of reversible physical cross‐linking. Some of the SA/P(AAm‐AAc‐OMA)‐Fe 3+ DPC hydrogels even exhibit a stretching‐induced strengthening effect, which is similar to the performance of muscle—"the more training, the more strength." Hence, the combination of HA and IC will provide an effective approach to design DPC hydrogels with desirable mechanical performances and a longer service life for wider applications of soft materials. Abstract : A dual physically cross‐linked (DPC) hydrogel with outstanding mechanical performances is prepared and investigated. The synergistic effect of two physical cross‐linkings endows DPC hydrogels with excellent modulus, strength, toughness, fatigue resistance, and self‐recoverability. In addition, the DPC hydrogels can exhibit a stretching‐induced strengthening effect, which is similar to the performance of muscle—"the more training, the more strength."